Environmental Sustainability in Infrastructure Construction—A Review Study on Australian Higher Education Program Offerings - Malindu Sandanayake; Yanni Bouras; Zora Vrcelj (Infrastructures, 2022)
Infrastructure advancement is a key attribute that defines the development and effective growth of a city or region. Since the introduction of the United Nations Sustainability Development Goals (UN SDGs), more construction companies are focusing on adopting sustainable construction practices. However, a lack of relevant competencies among employees at various infrastructure construction organizations often hinders the successful implementation of sustainable practices. Education that facilitates systematic professional development and contemporary competencies’ acquisition is a key to overcoming this barrier. Thus, the current study adopts a three-stage review to identify current research trends and inform future research directions for the enhancement of the environmental sustainability competencies base for infrastructure professionals. A bibliometric assessment was first conducted followed by a focused literature review on sustainability education. Subsequently, two engineering and construction higher education curricula were assessed for infrastructure sustainability content. The results from the three-step analysis indicate that the growing interest in sustainability concepts in the construction industry is driven by policy changes. A lack of financial incentives, the unavailability of resources, a lack of motivation amongst graduates, and limited time in the infrastructure construction sector were identified as some of the major impediments for developing the environmental sustainability competencies base. The requirement for integrated and structured Continuous Professional Development (CPD) programs to facilitate ongoing knowledge acquisition and structured evaluation of professional knowledge in addition to effective undergraduate program development are highlighted. The necessity for a digitally personalised platform that can graphically represent current progress and future milestones and enable peer interaction and collaboration was also identified as critical for improving the uptake of such programs. The findings from this study could be useful for government agencies and infrastructure construction organizations keen to enhance the environmental sustainability knowledge of their employees. Future studies are required to assess sustainability education across the globe and to develop new learning components of infrastructure sustainability that are validated through stakeholder participation.